(untitled) - Hamad, Munir M. (Hingham, Mass., 2010)
Includes AutoCAD2009 Demo on the DVD! Unlike many AutoCAD competitors, this book covers only the basics and uses mixed units _ inches, meters, feet, kilometers, etc., to illustrate the myriad drawing and editing tools for this popular application. AutoCAD 2009 Essentials includes 21 workshops, that complete small projects _ from concept through actual plotting. Solving all of the workshops will simulate the creation of a real life project from beginning to end, without overlooking any of the basic commands and functions in AutoCAD 2009.
Keywords: AutoCAD,Computer-aided design,Computer graphics